Liver Injury and Regeneration: Current Understanding, New Approaches, and Future Perspectives - Shainan Hora; Torsten Wuestefeld (Cells, 2023)
The liver is a complex organ with the ability to regenerate itself in response to injury. However, several factors can contribute to liver damage beyond repair. Liver injury can be caused by viral infections, alcoholic liver disease, non-alcoholic steatohepatitis, and drug-induced liver injury. Understanding the cellular and molecular mechanisms involved in liver injury and regeneration is critical to developing effective therapies for liver diseases. Liver regeneration is a complex process that involves the interplay of various signaling pathways, cell types, and extracellular matrix components. The activation of quiescent hepatocytes that proliferate and restore the liver mass by upregulating genes involved in cell-cycle progression, DNA repair, and mitochondrial function; the proliferation and differentiation of progenitor cells, also known as oval cells, into hepatocytes that contribute to liver regeneration; and the recruitment of immune cells to release cytokines and angiogenic factors that promote or inhibit cell proliferation are some examples of the regenerative processes. Recent advances in the fields of gene editing, tissue engineering, stem cell differentiation, small interfering RNA-based therapies, and single-cell transcriptomics have paved a roadmap for future research into liver regeneration as well as for the identification of previously unknown cell types and gene expression patterns. In summary, liver injury and regeneration is a complex and dynamic process. A better understanding of the cellular and molecular mechanisms driving this phenomenon could lead to the development of new therapies for liver diseases and improve patient outcomes.